Гадяцьке продовження "Літопису Грабянки" з 1758 р. (вступна стаття й публікація Д.Вирського) (Український історичний журнал, 2019)
Публікується специфічна історіографічна пам’ятка середини XVIII ст. (близько 1758 р.) у жанрі так званого козацького літописання, щойно віднайдена у фондах Інституту рукопису НБУВ. Документ походить із Гадяча і є витвором канцеляристів Гадяцького козацького полку. Текст має чимало пов’язань із «Літописом Грабянки», тож може вважатися його своєрідним продовженням (екстрактом-продовженням). Виклад обіймає період 1654–1742 рр. і містить окремі факти, досі невідомі історіографічній традиції. Твір також представляє собою ориґінальну форму поширення історичних знань в Україні доби Просвітництва («відомість» про військові походи). The article is devoted to the publication of the newly opened archival source (from the funds of the Institute of Manuscript of the V.Vernadskyi National Library of Ukraine). This is a specific historiographical text of the middle of the 18th century. (approx. 1758) in the genre of so-called Cossack chronicles. The text comes from Hadiach and is the creator of the regimental clerks of the Hadiach Cossack Regiment. The text has a lot of links with the “Chronicle of the Hrabianka” – a well-known historical work of the first half of the 18th century (the author of the Hadiach colonel Hryhorii Hrabianka), therefore, can be considered a kind of continuation (extraction-continuation). The historical event summary for 1654–1742 (actually for 1654, 1655, 1658, 1659, 1660, 1661,1662, 1663, 1664, 1665, 1666, 1667, 1668, 1669, 1670, 1671, 1672, 1674, 1675, 1677, 1678, 1679,1680, 1683, 1684, 1685, 1686, 1687, 1688, 1689, 1690, 1692, 1694, 1695, 1696, 1697, 1698, 1699,1700, 1701, 1702, 1703, 1704, 1705, 1706, 1707, 1708, 1709, 1710, 1711, 1713, 1714, 1715, 1716,1717, 1718, 1719, 1721, 1722, 1723, 1724, 1725, 1731, 1732, 1733, 1734, 1735, 1736, 1737, 1738,1739, 1740, 1742). They contains the individual facts of the still unknown for the historiographical tradition (especially interesting posts for 1659 – about election to Hetman Yurii Khmelnytskyi in Bratslav, for 1669 – about the battle of Hetman Petro Doroshenko and Hetman Petro Sukhovii at Sanzhariv in November 1668, for 1713, 1714, 1715, 1716, 1717 – about the activity of the Hadiach Regiment, for 1742 – about the campaign of Hadiach Colonel Petro Haletskyi). The historical work is also the original form of dissemination of historical knowledge in Ukraine of the Age of Enlightenment (“the note” on military campaigns).